An Ozone Reactor Design with Various Electrod Configurations - Agung Warsito; Abdul Syakur; Galuh Susilowati (Institute of Advanced Engineering and Science, 2011)
Environmental pollution is increasing, including water pollution due to industrial and household. To overcome this, there are three main concerns, namely the policy and environmental management, environmental awareness of society, and utilization of appropriate technologies to overcome pollution. This study is an attempt to overcome the problems of environmental pollution by designing, creating, and applying appropriate technology to make Ozone reactor with high-voltage corona discharge plasma technology. There are some methods of electrod configuration, namely wire-cylinder, spiral-cylinder, wire-cylinder with Dielectric Barrier Discharge (DBD), and spiral-cylinder with DBD. Corona discharge occurs between high-voltage electrod of each configuration ionize Oxygen flowed in the reactor, thus generating plasma and forming Ozone. The test of four Ozone reactors have been done by wastewater treatment in the form of soft drink samples, obtain the fading colors of wastewater, which is increasingly fade over many cycles of waste treatment process conducted in Ozon reactor. Based on comparison of four of Ozone reactor, it is obtained waste water treatment more maximal on reactor Ozone configuration of spiral-cylinder electrod with DBD. Keywords: Ozone reactor, electrods configuration, corona discharge, wastewaterDOI:http://dx.doi.org/10.11591/ijece.v1i2.79